Lipid profile and quality indices of ostrich meat and giblets - Antunes, Irene (2020)
In this study, the lipid profile of 5 different edible tissues (leg, thigh, heart, gizzard, and liver) of ostrich was analyzed. Ostrich edible tissues presented a low fat content (<5 g/100 g wet basis). Gizzard and heart revealed the highest amounts of total cholesterol (1.77 and 1.47 mg/g wet basis, respectively), differing significantly from all other tissues (which averaged 0.95 mg/g wet basis). The main tocochromanol in all tissues was alpha-tocopherol (10.3 mu g/g wet basis in heart and an average of 3.4 mu g/g wet basis for all the remaining tissues). All the samples presented a fatty acid profile, dominated by polyunsaturated fatty acids (PUFA) (>38%), namely, linoleic and arachidonic acids. The leg presented simultaneously the highest PUFA/saturated fatty acids (SFA), the lowest n-6/n-3 ratios, and the most favorable lipid quality indices among all tissues in comparison.